2020
DOI: 10.1186/s13071-020-04333-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a rhodanese homologue from Haemonchus contortus and its immune-modulatory effects on goat immune cells in vitro

Abstract: Background Modulation of the host immune response by nematode parasites has been widely reported. Rhodaneses (thiosulfate: cyanide sulfurtransferases) are present in a wide range of organisms, such as archaea, bacteria, fungi, plants and animals. Previously, it was reported that a rhodanese homologue could be bound by goat peripheral blood mononuclear cells (PBMCs) in vivo. Methods In the present study, we cloned and produced a recombinant rhodanese protein originating from Haemonchus contortus (rHCRD), a pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Besides, we also identified 5 H. contortus ESPs that interact with goat prey proteins with the highest frequency, including the chitin‐binding protein domain containing protein HCON_00008300 and rhodanese domain containing protein HCON_00106270. Previous studies found that a rhodanese homologue could be bound by goat PBMCs and suppress cell proliferation 73 . The 15 kDa protein HCON_00154030 also has more interactions with goat prey proteins.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Besides, we also identified 5 H. contortus ESPs that interact with goat prey proteins with the highest frequency, including the chitin‐binding protein domain containing protein HCON_00008300 and rhodanese domain containing protein HCON_00106270. Previous studies found that a rhodanese homologue could be bound by goat PBMCs and suppress cell proliferation 73 . The 15 kDa protein HCON_00154030 also has more interactions with goat prey proteins.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies found that a rhodanese homologue could be bound by goat PBMCs and suppress cell proliferation. 73 The 15 kDa protein HCON_00154030 also has more interactions with goat prey proteins. The H. contortus 15 kDa proteins are low molecular weight antigens, which can significantly suppress goat PBMCs proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that various HcESP-derived protein molecules, such as rHcMTF-12 [ 54 ], rHCRD [ 37 ], rHc-GDC [ 40 ], rHcEF-1α [ 46 ], rHcES-15 [ 34 ], rMiro-1 [ 55 ], HCcyst-3 [ 56 ] and RHC-AK [ 57 ], can bind to PBMCs in vitro and regulate cellular immune function. Our studies showed that rHcGOB can bind to goat PBMCs and activate the IL-10/TGF-β/STAT3 pathway in PBMCs in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The rHcGOB protein was purified and expressed as previously described [ 36 , 37 ]. The recombinant plasmid [pET28a(+) ligated with GOB] was transformed into Escherichia coli BL21(DE3) and cultured into Luria–Bertani medium containing kanamycin at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Major histocompatibility complex (MHC) molecule expression analysis was performed as previously described [ 35 ]. Freshly isolated monocytes (1 × 10 5 cells/ml per well) were seeded in 24-well cell culture plates containing complete RPMI 1640 medium.…”
Section: Methodsmentioning
confidence: 99%